Bibliometric Analysis of Library Hi Tech News (1983–2024): Publication Trends, Authorship, and Citation Patterns - Mondal, Debdas (Information Research Communications, 2026)
Purpose The purpose of this study is to conduct a comprehensive bibliometric analysis of Library Hi Tech News from 1983 to 2024 to examine its publication trends, authorship patterns, institutional productivity, thematic evolution, and scholarly impact. The study aims to highlight the journal’s contribution to research on library technologies and its influence within the Library and Information Science (LIS) domain. Design/Methodology/Approach The study adopts a quantitative bibliometric approach using data extracted from the Scopus database. Analytical indicators include annual publication growth, authorship patterns, author productivity, institutional and country-wise contributions, citation trends, and keyword co-occurrence. Data were organised using Microsoft Excel, while VOSviewer and Biblioshiny were employed to visualize collaboration networks and thematic structures. The analysis covers all relevant publications indexed between 1983 and 2024. Findings The results reveal a steady increase in publication output over four decades, reflecting the journal’s growing scholarly significance. Authorship analysis shows a shift from single-author publications toward collaborative research, while a core group of prolific authors significantly shapes the journal’s academic influence. Leading global institutions, particularly from the United States, United Kingdom, and India, contribute substantially to the journal’s output. Citation analysis identifies highly influential articles focused on digital libraries, RFID, e-learning, open access, and cloud technologies. Keyword co-occurrence mapping highlights evolving themes centered on digital innovation, automation, information literacy, and artificial intelligence. Originality This study represents the first comprehensive bibliometric assessment of Library Hi Tech News spanning four decades. By integrating publication trends, collaboration patterns, keyword evolution, and citation impact, the study provides a detailed understanding of the journal’s scholarly trajectory and thematic development. The findings offer valuable insights for researchers, practitioners, editors, and policy-makers seeking to understand technological advancements in the LIS field and future research directions.
Keywords: Library Hi Tech News; Bibliometric Analysis; Publication Trends; Authorship Pattern; Citation Analysis; Keyword Co-occurrence; Collaboration Network; Library Technology; Digital Libraries; Scopus.